2002
DOI: 10.1016/s0029-7844(02)01993-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of behavioral therapy on urinary incontinence: a randomized controlled trial

Abstract: A low-intensity behavioral therapy intervention for urinary incontinence was effective and should be considered as a first-line treatment for urinary incontinence in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(153 citation statements)
references
References 16 publications
3
148
1
1
Order By: Relevance
“…Table 3 details the trial arms compared against CBIs. Of the seven control comparisons, three were attention controls, 33,71,89 two were waitlist controls 90,91,100 and two were no treatment controls. 73,76 The remaining six treatment comparisons included three medications [propantheline bromide (Pro-Banthine ® , Roxane Laboratories Inc.) or oxybutinin (Ditropan, several manufacturers) (× 2)], 33,81,82,87 two single behavioural interventions (BT or PFMT) 31 and one psychotherapy comparison.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 details the trial arms compared against CBIs. Of the seven control comparisons, three were attention controls, 33,71,89 two were waitlist controls 90,91,100 and two were no treatment controls. 73,76 The remaining six treatment comparisons included three medications [propantheline bromide (Pro-Banthine ® , Roxane Laboratories Inc.) or oxybutinin (Ditropan, several manufacturers) (× 2)], 33,81,82,87 two single behavioural interventions (BT or PFMT) 31 and one psychotherapy comparison.…”
Section: Methodsmentioning
confidence: 99%
“…73,76 The remaining six treatment comparisons included three medications [propantheline bromide (Pro-Banthine ® , Roxane Laboratories Inc.) or oxybutinin (Ditropan, several manufacturers) (× 2)], 33,81,82,87 two single behavioural interventions (BT or PFMT) 31 and one psychotherapy comparison. 87 Seven of the trials were undertaken in the USA 31,33,73,76,[89][90][91]100 one in the UK, 87 one in Turkey 71 and one in Israel. 81,82 Three were quasi-RCTs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of nurse specialist proposed in this evaluation is responsible for urinary continence care and is specially trained to carry out physical examinations, prescribe drugs and containment products, and refer patients to specialist care. Effectiveness estimates of care provided by the nurse specialist in terms of improvement of the condition (mean 21%) and successfully treated (mean 31%) were based on a randomised controlled trial (RCT) by Subak et al [18]. The international awareness study [19] provided input for the estimations regarding the improvement of casedetection, as this study indicated that the majority of incontinence patients go undetected [16].…”
Section: Operationalisation Of the Optimum Continence Service Specifimentioning
confidence: 99%
“…It is thought that improved symptoms with bladder training may be attributed to a better understanding of the physiological responses of the bladder and the pelvic fl oor muscles. 24 When treating patients with cognitive or physical impairments, voiding programmes are generally used. These aim to offer increased toileting opportunities with assistance, together with assessment of toileting facilities and toileting aids.…”
Section: Smoking Cessationmentioning
confidence: 99%